(untitled) (Journal of Pharmaceutical Negative Results, 2015)
Picture archiving and communication systems (PACS) in radiology are an example of information technology systems used in healthcare that can improve productivity without sacrificing quality. The previous feedback loop between technologists and radiologists has been eliminated by the widespread use of PACS. Upon discovering quality discrepancies during an examination, the radiologist submitted a paper- based quality-control report rather than communicating the information directly. A web-based tool for reporting issues can facilitate the restoration of some of the feedback loop and offer opportunities for a more thorough examination of errors that users have submitted. This study set out to test the hypothesis that our department's efforts could be more concentrated if data from an online error reporting software used for quality control were utilized. 930 errors (390 exam protocol, 390 exam validation, and 150 exam technique) were submitted for the 372,258 radiologic examinations performed over the course of the 6- month study, translating to an error rate of 0.25%. Technologist documentation had the most submitted errors in the category exam protocol, with 77 errors [44%] in ultrasonography, and the highest subtype error for the computed tomography modality, with 35 errors [18%] in imaging protocol. For almost all of the modalities, positioning and incorrect accession had the highest errors in the exam technique and exam validation error categories, respectively. A system with a very high quality could be indicated by an error rate of less than 1%; however, it is more likely that some errors were missed or not reported. The reporting rate may also be impacted by how the error reporting system is received by the staff.